Structural and Functional Characterization of Campylobacter Jejuni Ferric Uptake Regulator (CjFur) - Sarvan, Sabina (Université d'Ottawa / University of Ottawa, 2018)
Transition metals are crucial components of several metabolic pathways and are critical for DNA, RNA and protein synthesis. However, when found in excess, these metal ions are toxic. To maintain the physiological concentration of metal ions at non-toxic concentration, bacteria rely on members of the Ferric uptake regulator (Fur) family of metalloregulators. Intriguingly, despite being coined as “metalloregulator”, specific members of the Fur family activate and repress gene expression in presence or absence of regulatory metals. Based on these observations, we hypothesized that the ability of these transcription factors to adopt different structural conformations underlies their ability to display different functions in presence and absence of metal ions. To address this important question, we solved the crystal structure of apo-Fur protein from Campylobacter jejuni. Structural analysis revealed that the protein adopts a V-shaped conformation harboring an evolutionary conserved cluster of positively charged residues on the surface. Using an extensive library of mutants and electrophoretic mobility shift analysis, we found that substituting residues forming the positively charged surface is detrimental for Fur interaction with DNA. Furthermore, our in vivo studies suggest that these positively charged residues are important for the regulation of CjFur target genes and that different mechanisms modulate the activity of Fur family of metalloregulators depending on the number of occupied metal binding sites. We showed that the disruption of metal binding sites of CjFur significantly reduces DNA binding in vitro and is deleterious for the repression of Fur target genes and gut colonization by C. jejuni. Finally, based on initial findings that adding a tag at the N-terminus of CjFur significantly reduces its ability to incorporate regulatory metal ions and bind DNA, we developed a new protocol for the purification of a highly active untagged CjFur protein. Overall, our studies shed new lights on the mechanistic basis controlling Fur gene regulatory activity in C. jejuni.
Keywords: X-ray crystallography; Transcription factor